TEACHING VOCABULARY USING CARTOON MOVIE - Ulfa, Fitria (IKIP Mataram, 2017)
The aim of this research is to know whether or not Cartoon Movie is effective in teaching vocabulary at the fifth grade students of SDN Bunklotok Batujai Lombok Tengah. The research is conducted for one month at the first semester year students of SDN Bunklotok Batujai Lombok Tengah. During the period of time, the sample is treated by using Cartoon Movie. The result of the research reveals that mean score of post-test is (15.93) higher than pre-test is (8.31). On the other hand, the standard deviation of posttest is (3.305) higher than pre-test is (2.523) under the identification of t-test formula, it is found that the value of it is 10.820 higher than t-table is (2.048), with the degree of freedom (df) was 29-1=28 for confidence level of 0.05% or 95%. From this point, it can be concluded that the alternative hypothesis is accepted stating that Cartoon Movie is effective in teaching English vocabulary for the fifth grade students of SDN Bunklotok Batujai Lombok Tengah.